Spontaneous Bilateral Septal Hematoma in Adult: An Unusual Case Presentation - Ahmad Farhan Fazal Kareem; Wan Ahmad Amiruddin Wan Hassan (International Journal of Human and Health Sciences (IJHHS), 2026)
Septal hematoma is an uncommon complication that is usually seen in a case of traumatic nasal bone fracture. However, it is very rare to have a spontaneuous septal hematoma. We report case of 44 years old Malay lady presented to us with complain of epistaxis, with worsening blockage, nasal pain and sneezing for past 5 days. However, she had no history of trauma. Rigid 0 degree nasoendoscopy done and noted septal swelling and felt bogginess upon palpation. Aspiration done noted 5cc blood seen. Incision and drainage done and bilateral nasal packing inserted. Patient was admitted in ward for observation and eventually discharged well. This case is important to highlight the clinical features and diagnostic challenges associated with septal hematoma, particularly when there is no history of trauma. This case report highlights the importance of early recognition and prompt management regardless unidentifiable cause in order to prevent from complications such as septal abscess, cartilage necrosis and saddle nose deformity. Above all, this is to raise awareness among clinicians about rare but potentially serious condition. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 297-299